QSOCKS: 0-RTT Proxification Design of SOCKS Protocol for QUIC - Madhan Raj Kanagarathinam (IEEE Access, 2020)
Multipath TCP (MPTCP) is an evolution of TCP, capable of using multiple network paths to enhance resilience to network handovers. However, Server-side modification is the key challenge for deployment of MPTCP on a large scale. Therefore, a proxy-based design that uses SOCKSv5 over MPTCP was proposed. Though MPTCP enhances the download experience, it also impacts the browsing experience and Page Loading Time (PLT) due to additional SOCKSv5 protocol signaling overhead. On the other hand, to improve the performance of TCP, Google proposed QUIC (Quick UDP Internet Connection), which addresses the network handover resilience. QUIC also faces server modification as a major challenge. In this article, we propose a novel design of SOCKS over QUIC (QSOCKS), which improves browsing experience while enhancing reliability. QSOCKS ensures 0RTT/1RTT connection time, thereby improving the Page Loading Time (PLT) and Video Loading Time (VLT). We evaluated the performance of QSOCKS through live experiments on the top websites of various web properties located in different regions, using Samsung S9 smartphones. Moreover, we evaluated our proposal for file download scenario in both homogeneous and heterogeneous Wi-Fi & cellular environment. The users not only benefit from the inherent advantages of QUIC but are also privileged with a better browsing experience.